APLIKASI SIG UNTUK PENENTUAN HIRARKI KLASIFIKASI FUNGSI JALAN DAN TINGKAT PELAYANAN (Level Of Service) RUAS JALAN TERHADAP PENGEMBANGAN POTENSI PARIWISATA DI KABUPATEN REMBANG (Geo-Image, 2015)
Improve network the way play an important role in area development especially in tourism potential .In regional development tourist destinations besides viewed from the perspective of road conditions there are also have to see from a variety of factors for example a hierarchy classifications function of road and the level of road service located in that area .System development road network right able to increase tourism potential .Efforts to improve the potency advancement tourism through the improvement of the road network system can be done by using the tools of geographical information system ( sig ) .Problems development transportation about the potential of tourism to do when want to optimize potential tourism potential .As for formulation of the study problems in this research is: ( 1 ) how a hierarchy the way based on classification systems function with based sig in the rembang district ( 2 ) how the impact of service ( the level of service Roads to development of tourism potential in the rembang district .Research locations is in the rembang district with the object research on the roads which includes the primary , a secondary way and local roads and tourism in the rembang district .Analysis the data used was with the methods scoring .Variable in this research was: ( 1 ) a class of the way , ( 2 ) the road , ( 3 ) the rate of service ( the level of service ) , ( 4 ) the location affordability tourism objects from a main line , ( 5 ) the distance routes with the object around it , ( 6 ) accessibility .)Â The results of the study can be seen that the division of a hierarchy of the function of jalan classification obtained based on the physical traits the road to the classification criteria the function of jalan according to adisasmita of which is divided into three parts those are the main highway / primary artery , secondary road primary / collector , local road or roads between the environment and service level ( los ) the lowest in the region roads intersection embung lodan kecamatan the hive with the value of los 0.12 that characterizes services characteristic of the level of a , while the value of los largest is found in roads sub-district village monokerto sale with a value of as much as 0,52 los that characterizes the level of services characteristic of c . The potency advancement tourism in the rembang district can be split into four categories class potential very high with 18.38 % which includes several subdistricts kaliori , the rembang , lasem and kragan .High potential 26.01 % covering several subdistricts sluke , the nest , pamotan and sulang , potential and 35,21 % included in pancur , sedan , sale and feathers .Potential low 20,40 % covering several subdistricts gunem and source of .Conclusion based on the results of research with the use sig it can be seen that a hierarchy classifications function of road in the rembang district is divided into three parts those are the main highway / primary artery , a secondary way / collector primary , local road or the way between environment . Reduced the real value los so level of road service the higher , which means the potency advancement wisatanya the higher to be developed as shown in the area tourism location embung lodan kecamatan the hive with value los 0.12 that characterizes characteristic level a service .